The Problems of the Relations between Religion and Policy in modern Kazakhstan (Journal of Philosophy Culture and Political Science, 2019)
In given article the problems of religion and politics in modern Kazakhstan are considered. It’s positive results have been presented. Inthe analyses of issues of current stage the main articles of Law of Republic Kazakhstan on “religious activity and religious associations”are used.